2010
DOI: 10.1128/aem.03068-09
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli of the Native cyt1Aa from Bacillus thuringiensis subsp. israelensis

Abstract: The gene cyt1Aa is one of the genes in the complex determining the mosquito larvicidity of Bacillus thuringiensis subsp. israelensis. Previous cloning in Escherichia coli resulted in a 48-bp addition upstream, encoding a chimera. Here, cyt1Aa was recloned without the artifact, and its toxicity against Aedes aegypti larvae and host E. coli cells was retested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This protein may be involved in post-translational processing (e.g., it may protect the nascent polypeptide from proteolysis by binding with it and allowing crystal formation) [46]. Moreover, p20 is known to increase the expression levels of other toxins such as Cyt1Aa, Cry1Ab, Cry1Ac, Cry2A, Cry3A, and truncated Cry1C proteins [34,50,51,52,53,54]. …”
Section: Other Known Crystallization Factorsmentioning
confidence: 99%
“…This protein may be involved in post-translational processing (e.g., it may protect the nascent polypeptide from proteolysis by binding with it and allowing crystal formation) [46]. Moreover, p20 is known to increase the expression levels of other toxins such as Cyt1Aa, Cry1Ab, Cry1Ac, Cry2A, Cry3A, and truncated Cry1C proteins [34,50,51,52,53,54]. …”
Section: Other Known Crystallization Factorsmentioning
confidence: 99%
“…Previous studies reported that the P20 helper protein is required for efficient expression of Cyt1Aa and other Cry toxins (Wu and Federici, 1993; Sazhenskiy et al ., 2010). As in this work we are interested in expressing different combinations of genes and in studying the interaction among different toxins of Bti, the p20 gene was maintained in the construct.…”
Section: Resultsmentioning
confidence: 99%
“…As the 20‐kDa helper protein was previously reported to be required for efficient expression of Cyt1Aa (Wu and Federici, 1993; Sazhenskiy et al ., 2010) and other Cry toxins (Shao et al ., 2001; Diaz‐Mendoza et al ., 2012; Elleuch et al ., 2015), the cry11Aa‐p20 construct was retained for further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the P20 appears to act as a chaperone to partially protect the host from the deleterious effects of Cyt1Aa, and although Cyt1Aa interacts with elements of the heat shock regulon, over-expression of groEL or groES does not substitute. A recent report has indicated that insecticidally active Cyt1Aa alone can be produced in E. coli using a tightly regulated promoter; however, there is still a dramatic reduction of cell viability upon induction (Sazhenskiy et al 2010). Interestingly, other structurally similar proteins can be well expressed in E. coli (Cohen et al 2008;Li et al 1996), suggesting, as expected, that sequence-specific protein interactions account for the Cyt1Aa expression defect.…”
Section: Pesticidal Protein Expression In Gram Negative Hostsmentioning
confidence: 86%